A generic multiCAD/multiPDM interoperability framework. (31st January 2011) - Paviot, Thomas; Lamouri, Samir; Cheutet, Vincent
Many Small and Medium Enterprises (SME) work as subcontractors (or co-contractors) for several clients for the design of mechanical components. During the design process, they must use a variety of Computer Aided Design (CAD) softwares and connect all the Product Data Management (PDM) systems of their customers. After defining the specific needs of these companies, we show that the available commercial CAD/PDM integrations, as well as the current literature, are inappropriate for a multiCAD/multiPDM collaborative design. We first define the few simple processes required to ensure an efficient collaboration. Then, the instantiation of these processes in our CAD/PDM integration can be split into four points: the general definition of a CAD product structure tree and its associated model, the conversion algorithm of the product structure to an Engineering Bill of Material (EBOM), the creation of an Unified Modelling Language (UML) data model, an implementation based upon Component Object Model (COM) and Service Oriented Architectures (SOA) technologies. We conclude by presenting the results obtained from the demonstrator developed.